Towards An Inclusive Energy Transition Beyond Coal - A comparison of just transition policies away from coal between China, the EU and the US. - Erpu Zhu; Loyle Campbell; Manfred Hafner; Xinqing Lu; Michel Noussan; Pier Paolo Raimondi (Fondazione Eni Enrico Mattei (FEEM), 2021)
This paper compares different just transition pathways in China, the European Union and the United States of America by comparing the current state of the coal sector and just transition policies away from coal. How can social justice in the energy transition be achieved under different models of energy governance? Since these three blocs have only made some progress on just transition policies and legislations for workers and communities impacted by the coal phase down or phase out in recent years, there have not been many studies comparing them to each other. The analysis in this paper shows that while all three blocs work towards ensuring the integration of coal workers and coal communities into the clean economy in the process of coal reduction, their approaches to achieving a just transition differ in terms of policy frameworks, financing resources, specific measures and public participation. This paper is part of a series of FEEM working papers of comparison studies of China, the EU and the US in the field of climate and energy.
Keywords: Q38; Q56; Q58; 330; Energy Transition; Just Transition; Coal Phase Out; Inclusiveness; China; the European Union; the United States